2023
DOI: 10.3389/fmicb.2023.1065823
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gut microbiota and Chinook salmon (Oncorhynchus tshawytscha) health and growth performance in freshwater recirculating aquaculture systems

Abstract: Gut microbiota play important roles in fish health and growth performance and the microbiome in fish has been shown to be a biomarker for stress. In this study, we surveyed the change of Chinook salmon (Oncorhynchus tshawytscha) gut and water microbiota in freshwater recirculating aquaculture systems (RAS) for 7 months and evaluated how gut microbial communities were influenced by fish health and growth performance. The gut microbial diversity significantly increased in parallel with the growth of the fish. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…Microbiota structures of the fin and kidney tissue from the present study were distinct from the structure of surrounding water microbiota, which was also the case for previous studies (67, 68). Although some bacteria derived from tissue overlapped with those of water microbiota, tissue microbiota often has specific bacterial consortia (20, 69).…”
Section: Discussionsupporting
confidence: 85%
“…Microbiota structures of the fin and kidney tissue from the present study were distinct from the structure of surrounding water microbiota, which was also the case for previous studies (67, 68). Although some bacteria derived from tissue overlapped with those of water microbiota, tissue microbiota often has specific bacterial consortia (20, 69).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the organization of gut bacterial community at the genus level was also observed, implying that Salmonella and Raoultella , as well as Bacteroides and Barnesiella , were most prevalent in the C and A samples, respectively. Mounting data indicated that they may be involved in inflammation, aging, and carbohydrate and short‐chain fatty acid metabolism (Borton et al., 2017 ; Fan et al., 2023 ; Li, Yang, et al., 2021 ; Zhao et al., 2023 ). Finally, we annotated the functional information of gut bacterial community from normal‐ and antibiotic‐fed A. viridicyanea when the results were compared with three databases, mainly including organic metabolism and biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…REN et al Li, Yang, et al, 2021;Zhao et al, 2023). Finally, we annotated the functional information of gut bacterial community from normal-and antibiotic-fed A. viridicyanea when the results were compared with three databases, mainly including organic metabolism and biosynthesis.…”
Section: Discussionmentioning
confidence: 99%